Application of SEAMON as Edible Bird’s Nest cleanser in the Edible Bird’s Nest Industry - Ningrum, Siti Gusti; Yulianto , Andreas Berny; Purnamasari, Kartika (Universitas Ahmad Dahlan, 2023)
Background: In Surabaya, the edible bird's nest industry has witnessed significant growth in recent years, driven by increasing demand for this highly prized delicacy, known for its nutritional and medicinal benefits. As the industry expands, effective cleaning methods for edible bird's nests become paramount. Contaminants, impurities, and feathers can compromise the quality and purity of edible bird's nests, affecting their market value and consumer appeal. Contribution: In response to this challenge, applying SEAMON as an edible bird's nest cleanser has emerged as a promising solution. SEAMON, a specific cleaning agent for edible birds' nests, offers the potential to revolutionize the cleaning process within the edible birds' nest industry. This innovative approach addresses the cleanliness and hygiene standards required for edible bird's nests, ensuring that consumers receive the highest quality product. Method: The SEAMON application was carried out at the edible bird's nest industry in Surabaya, East Java, on July 2, 2023, with twelve samples of edible bird's nests with heavy feather characteristics. All samples were tested for nitrite analysis using a Genesys 30 visible spectrophotometer. Results: Based on the results of its application, this innovation has the potential as an edible bird’s nest cleaning agent to clean hydrogen peroxide residue and can reduce nitrite levels in the white edible bird’s nest. Conclusion: This washing liquid is the first cleanser specifically for white edible bird’s nests, and another advantage is that it is food grade, so edible bird’s nests cleaned with SEAMON is safe for human consumption.